Faktor-Faktor yang Mempengaruhi Kepuasan Pemustaka di Perpustakaan Kopertis Wilayah X - Firma, Andriko; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
This paper focuse to the factors which influence satisfaction of the users in the Library of Kopertis Region X. This study aimed to describe the factors that influence satisfaction to the users Kopertis Region X. Data were collected through observation and interview to the visitors who came to the library of Kopertis Region X. The description of the data was analized by the research. It was concluded as the following. First, the librarians at the library of Kopertis Region X who has done a good job, although sometimes librarians have not been able to fully satisfy users. Second, the collection was not completely available in the Library of Kopertis Region X. Third, facilities and infrastructure in the Library of Kopertis Region X was also not completely available, such as tables and chairs that can be used to study and read.